Genome-Wide Association Study Reveals Novel Genomic Regions Associated With High Grain Protein Content in Wheat Lines Derived From Wild Emmer Wheat - Liu, Jia; Huang, Lin; Wang, Changquan; Liu, Yaxi; Yan, Zehong; Wang, Zhenzhen; Xiang, Lan; Zhong, Xiaoying; Gong, Fangyi; Zheng, Youliang; Liu, Dengcai; Wu, Bihua (Frontiers in Plant Science, 2019)
Grain protein content and grain yield are of important traits in wheat breeding, but their negative correlation has hampered the simultaneous improvement of these two traits in the conventional wheat breeding. Wild emmer wheat (Triticum turgidum ssp. dicoccoides) is an important genetic resource for increasing grain protein content (GPC) and improving other traits in modern cultivated wheat. In this study, we report a genome-wide association study (GWAS) using 13116 DArT-seq markers to characterize grain protein content in 161 wheat lines derived from wild emmer. The GPC and thousand kernel weight (TKW) of these lines were evaluated across three environments. We found that there was no significant negative correlation between GPC and TKW in the wild emmer derived lines. Using a general linear model, we identified 125 markers that were significantly associated with GPC, and grouped into 45 QTL regions. Using both general linear model and mixed linear model, we identified four significant markers and grouped into two large effect QTL regions on chromosomes 2BS and 7BL. Searches of public databases revealed 62 putative candidate/flanking genes related to GPC. The putative proteins of interest were grouped in four main categories: enzymes, kinase proteins, metal transport-related proteins, and tolerance response proteins. The linked markers and associated candidate genes provide essential information for cloning genes related to high GPC and performing marker-assisted breeding in wheat.